Ability Of Mathematical Reasoning in SMK 10th Grade with LAPS- Heuristic using Performance Assessment - Arivina, Aulia Nur; Masrukan, Masrukan; Prabowo, Ardhi (Unnes Journal of Mathematics Education, 2017)
The purposes of this research are: (1) Test the learning with LAPS-Heuristic model using performance assessment on 10th grade of Trigonometry material is complete, (2) to test the difference of students' mathematical reasoning ability on 10th grade of Trigonometry material between the learning model of LAPS-Heuristic using performance assessment, LAPS-Heuristic learning model with Expository learning model, (3) test the ability of mathematical reasoning with learning model of LAPS-Heuristik on Trigonometry material of SMK on 10th grade using performance assessment is increase. This is a quantitative research. The population is students of 10th grade of SMK 10 Semarang academic year 2016/2017 and the subject of research is selected by clustering random sampling. The results show that (1) Learning by model LAPS-Heuristic using performance assessment on 10th grade of Trigonometry material is complete (2) there are differences in students' mathematical reasoning ability on 10th grade of Trigonometry materials between LAPS-Heuristic learning model using performance assessment, LAPS-Heuristic learning model, and Expository learning model, (3) The ability of mathematical reasoning with learning model of LAPS-Heuristic on Trigonometry material of SMK class X using performance assessment increased.